Yumi Tok Stori: A Papua New Guinea Melanesian Research Approach - Bolinga, Catherina (Waka Kuaka, 2023)
The tok stori research approach is described as a Melanesian informal meeting including a storytelling session that enables embedded information to be released through conversation and, as the literature suggests, is contextually flexible. This paper looks at using the tok stori approach in research contexts with Papua New Guinea (PNG) communities in Aotearoa New Zealand and endeavours to contextualise tok stori by explaining how it is used in the PNG community contexts from where it originated. When the term tok stori is used alone, it is a verb that indicates an informal storytelling meeting in a social context with conversation. When contextualising tok stori using PNG Tok Pisin in most group meeting settings, the term tok stori alone does not convey invitation and inclusivity; therefore, a pronoun must be added to convey this for an informal (or formal) meeting. In this case, the pronoun yumi (you and me, you and us) is used. Yumi tok stori can be used for one-on-one and group meetings. Writing about tok stori and its application in various contexts and situations will enable this approach to be revised and rendered relevant in its applicability rather than used only as a generic approach given the variations in the pidgin creoles spoken in the different pidgin-speaking countries in Oceania.